Enhanced carbon dioxide biomethanation with hydrogen using anaerobic granular sludge and metal–organic frameworks: Microbial community response and energy metabolism analysis. (October 2022) - Dong, Zhiwei; Ding, Yudong; Chen, Fei; Zhu, Xun; Wang, Hong; Cheng, Min; Liao, Qiang
Graphical abstract: Highlights: Metal organic frameworks (MOFs) significantly promote CO2 biomethanation with H2 . MOFs promote direct interspecific electron transfer between microorganisms. Hydrogenotrophic methanogens were enriched in the anaerobic reactors with MOFs. MOFs alleviated the hydrogen competition of bacteria. MOFs increase the abundance of functional gene for CO2 biomethanation with H2 . Abstract: In this work, metal–organic frameworks (MOFs) were prepared to evaluate its impact on carbon dioxide (CO2 ) biomethanization during anaerobic degradation (AD). The results showed that MOFs significantly improved the CO2 biomethanation efficiency, especially in the AD reactors using a concentration of 1.0 g/L MOFs. Furthermore, MOFs promoted direct interspecific electron transfer and alleviated the hydrogen competition of bacteria. Meanwhile, hydrogenotrophic methanogens were enriched in the AD reactors with MOFs. After the addition of MOFs, there was 3.28 times and 3.41 times increase in the abundance of metabolic functions related to methanogenesis by CO2 reduction with hydrogen and dark hydrogen oxidation, respectively. There was an increased abundance of all genes that encode the key enzymes used in methane metabolism. However, functional genes involved in nitrate reduction had their expressions inhibited. The work may offer a contribution to helping the industry achieve the carbon capture and utilization policy.